2019
DOI: 10.5817/sp2019-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Images of the Ideal Student as a Marker for School Culture and Its Role in School Alienation During the Transition from Primary to Secondary Education in Luxembourg

Abstract: Particularly in highly stratified educational systems, the transition from primary to secondary school involves a substantial alteration of school culture as students leave their familiar environment of primary school and encounter a fundamentally different, initially strange school context. The transition to a new secondary school culture is presumably one cause of students' increasing school alienation as the students face specific expectations from their secondary teachers. The main aim of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…This may mirror the manifold measures in the Luxembourgish system to increase wellbeing, but to keep achievement pressure low in educational settings with a high proportion of low SES students. Qualitative research indicated that the higher school alienation relates to the higher achievement aspiration, while in the low-achievement track Modulaire, the absence of a strong achievement motivation may come with a lower school alienation (Grecu, Hascher, and Hadjar 2019). Another argument could relate to differential degrees of critical thinking: as high SES students come from more highly educated families, and instruction and learning content in academic tracks (ES) foster intelligence and cognitive mobilisation (Guill, Lüdtke, and Köller 2016) as well as political thinking, engagement and discussion (Nieuwelink, Dekker, and ten Dam 2019), students in academic tracks tend to be more critical about their school environment.…”
Section: Discussionmentioning
confidence: 99%
“…This may mirror the manifold measures in the Luxembourgish system to increase wellbeing, but to keep achievement pressure low in educational settings with a high proportion of low SES students. Qualitative research indicated that the higher school alienation relates to the higher achievement aspiration, while in the low-achievement track Modulaire, the absence of a strong achievement motivation may come with a lower school alienation (Grecu, Hascher, and Hadjar 2019). Another argument could relate to differential degrees of critical thinking: as high SES students come from more highly educated families, and instruction and learning content in academic tracks (ES) foster intelligence and cognitive mobilisation (Guill, Lüdtke, and Köller 2016) as well as political thinking, engagement and discussion (Nieuwelink, Dekker, and ten Dam 2019), students in academic tracks tend to be more critical about their school environment.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanismen hinter dieser Entwicklung sind neben der zunehmenden Adoleszenz sicher auch die sich mit dem Übergang von der Grund-in die Sekundarschule verändernden Schulumwelten und Lehrstile sowie insbesondere die über die Sekundarbildung zunehmenden Leistungsanforderungen (vgl. Grecu et al 2019).…”
Section: Allgemeine Lebenszufriedenheitunclassified
“…Alienation and social justice leadership in terms of the powerlessness. Excluding students from decision making regarding the rules and processes at school can cause alienation, as it will create the feeling that school life is guided by others (Grecu et al, 2019). This situation reveals alienation in the dimension of powerlessness.…”
Section: Conceptual Framework: the Relationship Between Social Justic...mentioning
confidence: 99%